Mothers’ Perceptions Based on the Health Belief Model Regarding Exclusive Breastfeeding and Stunting Prevention - Pangaribuan, Ingka Kristina; Sibarani, Lisa Erawati; Sinaga, Rosmani; Manurung, Herna Rinayanti; Sinaga, Siti Nurmawan; Rachmat, Ade; Lubis, Adi Raja Brando (Journal of Maternal and Child Health Sciences (JMCHS), 2025)
Sustainable Development Goal (SDG) number two aims to create a healthy and productive society free from hunger. According to SDG data, the stunting rate among children under five decreased from 24.4% in 2021 to 21.6% in 2022. However, disparities remain across provinces, and national targets have not yet been achieved. Stunting is characterized by a Z-score less than -2 SD (moderate) and less than -3 SD (severe). One of the main obstacles to achieving this goal is the prevalence of malnutrition among children under five, which is a major factor contributing to stunting (1). This study aims to explore mothers' perceptions using the Health Belief Model (HBM) regarding exclusive breastfeeding in preventing. The research method is analytical, using a cross-sectional design with a Chi-Square test to analyze the influence between variables. The population consists of all mothers with toddlers, with a total of 149 visits recorded in the past year. A sample of 60 mothers was selected. Primary data were collected using questionnaires, and secondary data were obtained through interviews. The results showed that most respondents were aged 31–40 years (66.7%), had a high school education (66.7%), and were housewives (91.7%). There was a statistically significant relationship between perceived susceptibility (p=0.009) and perceived severity (p=0.024) with the practice of exclusive breastfeeding in preventing stunting. Conclusion: There is a significant relationship between mothers' perceptions of susceptibility and severity. Educational interventions should focus on enhancing mothers’ positive perceptions of the importance of exclusive breastfeeding